Attitude toward Prenatal Testing and Termination of Pregnancy among Health Professionals and Medical Students in Saudi Arabia - A. Gaboon, Nagwa E.; Bakur, Khadijah H.; Edrees, Alaa Y.; Al-Aama, Jumana Y. (Journal of Pediatric Genetics, 2017)
This study was aimed at assessing the attitude of health care professionals in Jeddah city toward prenatal diagnosis (PND) and termination of pregnancy (TOP). A cross-sectional study was conducted, and the participants completed a self-administered questionnaire. Approximately 82% of participants showed a consistent trend of accepting PND when appropriate, and 47.5% of the respondents were in favor of TOP if the fetus had a severe disease. Compared with men (69.3%), a significantly greater number of women (88%) accepted to have PND. The most acceptable prenatal diagnostic tests in the study were invasive techniques as most of the participants thought that noninvasive tests were nonspecific.
Keywords: prenatal diagnosis; termination of pregnancy; noninvasive procedures; invasive procedures